Cytological and Molecular Mechanism of Low Pollen Grain Viability in a Germplasm Line of Double Lotus - Guangyang Liu; Fengjun Liu; Huiyan Jiang; Jun Li; Jing Jing; Qijiang Jin; Yanjie Wang; Ping Qian; Yingchun Xu (Plants, 2023)
Self-fertilization rate is an essential index of lotus reproductive system development, and pollen activity is a key factor affecting lotus seed setting rate. Based on cytology and molecular biology, this study addresses the main reasons for the low self-set rate of double lotus. It takes two different double lotus breeds into consideration, namely ‘Sijingganshan’ with a low self-crossing rate and ‘Jinfurong’ with a high self-crossing rate. Cytological analysis results showed that the pollen abortion caused by excessive degradation of tapetum during the single phase was the root cause for the low self-mating rate of double lotus. Subsequent transcriptome analysis revealed that the gene NnPTC1 related to programmed tapetum cell death was significantly differentially expressed during the critical period of abortion, which further verified the specific expression of NnPTC1 in anthers. It was found that the expression level of NnPTC1 in ‘Sijingganshan’ at the mononuclear stage of its microspore development was significantly higher than that of ‘Jinfurong’ at the same stage. The overexpression of NnPTC1 resulted in the premature degradation of the tapetum and significantly decreased seed setting rate. These results indicated that the NnPTC1 gene regulated the pollen abortion of double lotus. The mechanism causing a low seed setting rate for double lotus was preliminarily revealed, which provided a theoretical basis for cultivating lotus varieties with both flower and seed.